(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Patient satisfaction is a critical indicator of healthcare quality, especially in infertility treatment, which involves high costs and significant psychological stress. This study aims to assess satisfaction levels and related factors at the Center for Assisted Reproduction and Tissue Engineering, Hanoi Medical University Hospital. Methods: A cross-sectional descriptive study was conducted on 130 female clients undergoing In Vitro Fertilization (IVF) cycles from May 2025 to July 2025. Data were collected using a structured questionnaire based on the PCQ-Infertility scale and WHO framework, utilizing a 5-point Likert scale. Results: The mean age of participants was 32 ± 5.2 years; the majority held university/postgraduate degrees (92.31%). The overall mean satisfaction score reached 21.1 ± 3.06 (out of 25). Clients reported the highest level of satisfaction with "Perceived Outcomes" (4.47 ± 0.25) and the lowest with "Treatment Costs" (3.9 ± 0.69). Multivariable regression analysis, after adjusting for confounding variables, demonstrated that educational level and average monthly income were significantly and negatively associated with satisfaction scores (p < 0.05). This suggests that intellectual and high-income clients tend to have more stringent expectations. Other factors, such as the duration of infertility and age, did not reach statistical significance in the multivariable model (p > 0.05) Conclusion: IVF service quality is highly rated, particularly regarding professional trust and staff attitude. However, improvements in financial counseling and care coordination continuity are needed to optimize patient experience.